X-ray properties of high-richness CAMIRA clusters in the Hyper Suprime-Cam Subaru Strategic Program field. (7th November 2019) - Ota, Naomi; Mitsuishi, Ikuyuki; Babazaki, Yasunori; Akamatsu, Hiroki; Ichinohe, Yuto; Ueda, Shutaro; Okabe, Nobuhiro; Oguri, Masamune; Fujimoto, Ryuichi; Hamana, Takashi; Miyaoka, Keita; Miyazaki, Satoshi; et al.
Abstract: We present the first results of a pilot X-ray study of 37 rich galaxy clusters at 0.1 < z < 1.1 in the Hyper Suprime-Cam Subaru Strategic Program field. Diffuse X-ray emissions from these clusters were serendipitously detected in the XMM-Newton fields of view. We systematically analyze X-ray images of 37 clusters and emission spectra of a subsample of 17 clusters with high photon statistics by using the XMM-Newton archive data. The frequency distribution of the offset between the X-ray centroid or peak and the position of the brightest cluster galaxy was derived for the optical cluster sample. The fraction of relaxed clusters estimated from the X-ray peak offsets in 17 clusters is 29 ± 11(±13)%, which is smaller than that of the X-ray cluster samples such as HIFLUGCS. Since the optical cluster search is immune to the physical state of X-ray-emitting gas, it is likely to cover a larger range of the cluster morphology. We also derive the luminosity–temperature relation and found that the slope is marginally shallower than those of X-ray-selected samples and consistent with the self-similar model prediction of 2. Accordingly, our results show that the X-ray properties of the optical clusters are marginally different from those observed in the X-ray samples. The implication of the results and future prospects are briefly discussed.